18F-AV-1451 tau PET imaging correlates strongly with tau neuropathology in MAPT mutation carriers - Smith, Ruben; Puschmann, Andreas; Schöll, Michael; Ohlsson, Tomas; van Swieten, John; Honer, Michael; Englund, Elisabet; Hansson, Oskar (Brain (London, England : 1878), 2016)
Tau positron emission tomography ligands provide the novel possibility to image tau pathology in vivo However, little is known about how in vivo brain uptake of tau positron emission tomography ligands relates to tau aggregates observed post-mortem. We performed tau positron emission tomography imaging with (18)F-AV-1451 in three patients harbouring a p.R406W mutation in the MAPT gene, encoding tau. This mutation results in 3- and 4-repeat tau aggregates similar to those in Alzheimer's disease, and many of the mutation carriers initially suffer from memory impairment and temporal lobe atrophy. Two patients with short disease duration and isolated memory impairment exhibited (18)F-AV-1451 uptake mainly in the hippocampus and adjacent temporal lobe regions, correlating with glucose hypometabolism in corresponding regions. One patient died after 26 years of disease duration with dementia and behavioural deficits. Pre-mortem, there was (18)F-AV-1451 uptake in the temporal and frontal lobes, as well as in the basal ganglia, which strongly correlated with the regional extent and amount of tau pathology in post-mortem brain sections. Amyloid-β ((18)F-flutemetamol) positron emission tomography scans were negative in all cases, as were stainings of brain sections for amyloid. This provides strong evidence that (18)F-AV-1451 positron emission tomography can be used to accurately quantify in vivo the regional distribution of hyperphosphorylated tau protein.